2016
DOI: 10.1080/17550874.2016.1185653
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of selective logging on dipterocarp populations in the Pasoh Forest Reserve, Malaysia

Abstract: Background: Selective logging alters tree growth, mortality and recruitment, and the subsequent population dynamics of trees. However, little information is available on how tree populations reduce local extinction in logged forests. Aims: We evaluated the effects of selective logging on tree performance and population dynamics of five dominant dipterocarp species in the Pasoh Forest Reserve, Malaysia. Methods: We used demographic data derived from a forest that was selectively logged in 1958 as well as those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 40 publications
1
9
0
Order By: Relevance
“…However, we observed a population declined during the study period. That is to say, if forests are exposed to under continuous logging management practices, pioneer species with a similar demography to P. massoniana may experience a population decline and even disapperar altogether due to low seedling recruitment (Hastings 2001;Yamada et al 2016). On the other hand, previous studies have shown that it can take years or even decades for the influence of logging to be seen on long-lived tree populations (Bonnell et al 2011;Egnell and Valinger 2003).…”
Section: Management Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we observed a population declined during the study period. That is to say, if forests are exposed to under continuous logging management practices, pioneer species with a similar demography to P. massoniana may experience a population decline and even disapperar altogether due to low seedling recruitment (Hastings 2001;Yamada et al 2016). On the other hand, previous studies have shown that it can take years or even decades for the influence of logging to be seen on long-lived tree populations (Bonnell et al 2011;Egnell and Valinger 2003).…”
Section: Management Implicationsmentioning
confidence: 99%
“…It has been shown that the successful regeneration of pioneer species has a positive correlation to canopy gaps (Arets et al 2003). However, for shade-tolerant species, logging could have a significant impact on population dynamics through a reduction in recruitment, which could even cause extinction if exposed to periodic regime (Yamada et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies noted above addressed some aspects of forest disturbance or fragmentation. Ang et al (2016) showed how logging had minimal impacts on seedling genetic diversity and Yamada et al (2016) also found that logging did not impact tree growth rates or mortality but did influence recruitment. A number of studies used the small Bukit Timah Nature Reserve and surrounding secondary forest as examples of fragmented forest within an urbanised matrix (Corlett 1992) that may represent an extreme fate of dipterocarp forests in the future.…”
Section: Disturbance and Fragmentationmentioning
confidence: 99%
“…Timber extraction has been extensive in the past, and long-lived taxa, such as the dipterocarps, may have a 'disturbance memory' of such perturbations, transcending generations and lasting decades or hundreds of years (e.g. Yamada et al 2016).…”
Section: Moving Forward: Applying Autecological Knowledge Of Dipterocmentioning
confidence: 99%
See 1 more Smart Citation